The homeschooling handbook : how to make homeschooling simple, affordable, fun, and effective - Lippincott, Lorilee (Skyhorse Publishing, 2014)
"The mere thought of homeschooling can be overwhelming. What curriculum do I choose? What if we can't afford all the books? How do I schedule our time? Will my children become socially awkward recluses? What if I screw up my kids' education?! Lorilee Lippincott, a seasoned homeschooling mom, shows just how simple homeschooling can be. But homeschooling well does require some planning and dedication, and a book like The Homeschooling Handbook to be your guide. Here you'll find all your questions answered in Lippincott's straightforward, warm, and witty style"--